ANALYSIS OF FINANCIAL DISTRESS USING THE ALTMAN Z-SCORE MODEL IN PT SIDO MUNCUL TBK IN THE PERIOD 2020-2022 - Ari Kharisma (Asosiasi Dosen Muda Indonesia, 2023)
This research aims to analyze the potential for financial distress in PT Sido Muncul Tbk for the 2020-2022 period by using five financial variables in the Altman Z-Score model. The variables are Working Capital to Total Assets (X1), Retained Earnings to Total Assets (X2), Earnings before Interest and Taxes to Total Assets (X3), Market Value of Common and Preferred Stock to Book Value of Total Debt (X4), and Sales to Total Assets (X5). This research is quantitative with secondary data sources of PT Sido Muncul Tbk. The research data used are annual financial reports for 2020-2022. The annual financial report from the company's official website and the website of the Indonesia Stock Exchange (IDX). This study used the Altman Z-Score method to analyze financial distress in companies. The result is PT Sido Muncul Tbk’s increase in the Z-Score value every year with a Z-Score value > 2.99 for 2020-2022. Based on the cut-off point of the Altman Z-Score method for PT Sido Muncul Tbk is in a safe zone. A company with a safe zone is one that the company is a good financial condition and has great potential in developing its business and getting more advanced in business activities over the next few years.